Hubungan Pola Asuh Orang Tua dengan Motivasi Belajar Siswa Tunagrahita di SLB BC Dharma Wanita 03 Malang - Mega Putriatul Chusna; Mohammad Efendi; Ediyanto Ediyanto (Universitas PGRI Semarang, 2022)
Parenting parents play an essential role in developing children's learning motivation. However, children with intellectual disabilities often experience failure, which causes children to despair quickly. Under these conditions, children with intellectual disabilities need appropriate parenting to develop learning motivation. This study aims to determine the relationship between parenting style (X2) and learning motivation of intellectual disabilities students (X2) at SLB BC Dharma Wanita 03 Negeri Malang. This research was conducted with quantitative methods using a correlational research design. Questionnaires and interviews did data collection. The data were analyzed by Spearman rank correlation analysis. The study results: there is a significant relationship between parenting patterns (X1) and learning motivation of intellectual disabilities students (X2) with a Spearman Rho correlation value of 0.872 with a significance level of 0.001. This study concludes that there is a positive and direct relationship between parenting patterns (X1) and the learning motivation of intellectual disabilities students (X2) and has a strong relationship.